Literacy Program to Foster Reading Habits from an Early Age for Madrasah Ibtidaiyah Students - Al-Manduriy, Shahibul Muttaqien; Guntur; Millatur Rahmah Syafi’i (Global Action and Education for Society, 2025)
This study aims to describe the implementation of a literacy program to introduce early reading habits for Madrasah Ibtidaiyah Students and analyse its impact on students' reading interest. The background of this research is based on the low literacy culture of Indonesian students and the importance of fostering early reading habits as a foundation for learning and character development. The approach used in this study was qualitative with descriptive methods. Data collection techniques were conducted through interviews, observation, and documentation. The research subjects included the principal, literacy mentor teachers, students, and parents in Madrasah Ibtidaiyah. The results show that the literacy program at Madrasah Ibtidaiyah Students is implemented through various strategies, such as a 15-minute reading habit, story reading by teachers, the provision of reading boxes in each classroom, and parental involvement. This program has been proven to increase students' interest in reading, as evidenced by changes in student behaviours, who have begun actively reading during their free time, and increased student comprehension of the reading material. Challenges faced in program implementation include limited facilities, lack of teacher training, and a lack of engaging reading materials. However, active teacher participation and parental support are crucial factors in the success of this literacy program. This research recommends developing more engaging literacy resources and establishing reading communities, such as book clubs, to strengthen the reading culture among students. Thus, literacy programs not only play a role in improving reading skills but also serve as a foundation for students' character and love of knowledge